Enhanced stability of sodium metal anodes in covalent triazine frameworks via progressive nucleation with optimized conducting composite matrix - Wasnik, Kundan; Bhatt, Rajesh C.; Shelke, Manjusha V. (Small, 2025)
Organic materials offer exciting possibilities to improve rechargeable battery performance in multiple ways. This study explores the Covalent Triazine Framework (CTF) as an interlayer to modulate progressive sodium nucleation and subsequent recurrent deposition/extraction in an anode-less sodium battery. The optimized composite, C60R40, which combines CTF with reduced graphene oxide (rGO), has demonstrated its effectiveness as a host. In half cell Na electrodeposition, the C60R40 host exhibits 99.9% coulombic efficiency at an applied current density and areal capacity of 6 mA cm-2 and 2 mAh cm-2, respectively, for 500 cycles. The stable performance is also observed in both full-cell and anode-less battery configurations. When paired with Na3V2(PO4)2F3, the sodium-plated C60R40 demonstrated a stable discharge capacity of 110 mAh g-1. Furthermore, the anode-less sodium battery configuration, with Na3V2(PO4)3 cathode, achieved a promising discharge capacity exceeding 50 mAh g-1 without any additional modifications. These findings highlight the significant role of organic materials in improving the performance of rechargeable sodium metal batteries.
Keywords: anode-less batteries; CTF; instantaneous and progressive nucleation; Nucleation and growth; SEI